On-Surface Synthesis of Highly Oriented Thin Metal–Organic Framework Films through Vapor-Assisted Conversion - Virmani, Erika; Rotter, Julian M; Mähringer, Andre; von Zons, Tobias; Godt, Adelheid; Bein, Thomas; Wuttke, Stefan; Medina, Dana D (Journal of the American Chemical Society, 2018)
Controlled on-surface film growth of porous and crystalline frameworks is a central prerequisite for incorporating these materials into functional platforms and operational devices. Here, we present the synthesis of thin zirconium-based metal–organic framework (MOF) films by vapor-assisted conversion (VAC). We established protocols adequate for the growth of UiO-66, UiO-66(NH2), UiO-67, and UiO-68(NH2) as well as the porous interpenetrated Zr–organic framework, PPPP–PIZOF-1, as highly oriented thin films. Through the VAC approach, precursors in a cast solution layer on a bare gold surface are reacting to form a porous continuous MOF film, oriented along the [111] crystal axis, by exposure to a solvent vapor at elevated temperature of 100 °C and 3 h reaction time. It was found that the concentration of dicarboxylic acid, the modulator, the droplet volume, and the reaction time are vital parameters to be controlled for obtaining oriented MOF films. Using VAC for the MOF film growth on gold surfaces modified with thiol SAMs and on a bare silicon surface yielded oriented MOF films, rendering the VAC process robust toward chemical surface variations. Ethanol sorption experiments show that a substantial part of the material pores is accessible. Thereby, the practical VAC method is an important addition to the toolbox of synthesis methods for thin MOF films. We expect that the VAC approach will open new horizons in the formation of highly defined functional thin MOF films for numerous applications.